Afro-American Student Union [fundraiser booth] (1988)
Five Black students are behind a booth for the Afro-American Student Union. The sign above the booth reads 'Soda 60 cents' and an unidentified food item priced at $1.50. Two other Black students are next to the booth towards the front.